Resiko Dalam Bisnis Peternakan: Konseptual Berbasis Teori Maqashid - Ningrum, Eka Rahayu Puspita; Wahyudi, Amin (Universitas Islam Negeri Alauddin Makassar, 2023)
Risk is a certainty that cannot be trusted. Every risk inherent in life will be diverse and varied settlement solutions. Likewise in animal husbandry which is often a problem. Risk management on farms in the perspective of maqashid syariah is a must. Because animal husbandry is actually a profitable business but also a high potential risk. This study aims to describe risk management from the perspective of sharia maqashid which focuses on livestock business which is considered as an unstructured business and regulations that are the solution. This study used description analysis with library research method. The results showed that there are several risks to livestock, one of which is financial risk. In the concept of maqashid sharia, the main purpose of carrying out economic activities is not only limited to financial benefits but is benefit with the value of welfare and goodness of life. The concept of sharia maqashid also advocates an element of prudence in running a livestock business to avoid uncertainty. In this case, researchers found one of the regulations that is a solution to the financial risks in livestock businesses, namely sharia-based livestock insurance.